Penerimaan Masyarakat terhadap Website P3M.Sidoarjokab.go.id - Dyah Ary Setya Ningrum; Ainur Rochmaniah (Kanal: Jurnal Ilmu Komunikasi, 2016)
This study aimed to describe community reception of website P3M.sidoarjokab.go.id. This research used descriptive qualitative method with in-depth interview technique. The focus of this research discussed perception, thinking, preference, interpretation, ease of use, easy of finding information, design of page, web traffic and search in website of Complaint Service Center (P3M). Data analysis technique in this research used interactive analysis, with five informant. The research found that P3M website had applied ease of use dimension and web traffic and search well. P3M website had facilitated the user at the time that would report with the ease of features and access, and facilitate the user at the time that would search the website in search engines. P3M websites were still lack in applying the easy of finding information and design of page dimensions. Images in the website was still very poor so could not support information and website design P3M was still very monotonous and not interesting.